The gut microbiota: A new perspective for tertiary prevention of hepatobiliary and gallbladder diseases - Huang, Xiaoyu; Yang, Yi; Li, Xueli; Zhu, Xiaoya; Lin, Dan; Ma, Yueran; Zhou, Min; Cui, Xiangyi; Zhang, Bingyu; Dang, Dongmei; Lü, Yuhong; Yue, Changwu (Frontiers in Nutrition, 2023)
The gut microbiota is a complex ecosystem that has coevolved with the human body for hundreds of millions of years. In the past 30 years, with the progress of gene sequencing and omics technology, the research related to gut microbiota has developed rapidly especially in the field of digestive system diseases and systemic metabolic diseases. Mechanical, biological, immune, and other factors make the intestinal flora form a close bidirectional connection with the liver and gallbladder, which can be called the “gut–liver–biliary axis.” Liver and gallbladder, as internal organs of the peritoneum, suffer from insidious onset, which are not easy to detect. The diagnosis is often made through laboratory chemical tests and imaging methods, and intervention measures are usually taken only when organic lesions have occurred. At this time, some people may have entered the irreversible stage of disease development. We reviewed the literature describing the role of intestinal flora in the pathogenesis and biotherapy of hepatobiliary diseases in the past 3–5 years, including the dynamic changes of intestinal flora at different stages of the disease, as well as the signaling pathways involved in intestinal flora and its metabolites, etc. After summarizing the above contents, we hope to highlight the potential of intestinal flora as a new clinical target for early prevention, early diagnosis, timely treatment and prognosis of hepatobiliary diseases. GRAPHICAL ABSTRACT